Understanding Turkey's Kurdish question - Bilgin, Fevzi; Sarıhan, Ali (Lexington Books, 2013)
This volume, comprising chapters by leading academics and exports, delves into the complicated nature of Turkey's Kurdish issue. The volume discusses the evolution of Kurdish nationalism, the contemporary Kurdish movement and its violent legacy, civil society efforts in Turkey's Kurdish region, and the international dimensions of the Kurdish question.
Keywords: Kurdish question -- Turkey.; Kurds -- Turkey -- History.; Kurds -- Turkey -- Politics and government.; Kurds -- Turkey -- History -- Autonomy and independence movements.; Turkey -- Ethnic relations.; Asie Mineure -- Relations interethniques.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Ethnic Studies -- General.; SOCIAL SCIENCE -- Minority Studies.; Ethnic relations; Kurdish question; Kurds; Kurds -- Autonomy and independence movements; Kurds -- Politics and government; Turkey; History